ANGULAR CHEILITIS: A MULTIDISCIPLINARY APPROACH TO DIAGNOSIS AND MANAGEMENT - Oana Mihaela Condurache Hritcu; Mihaela Paula Toader; Ana Maria Sciuca; Bianca Andreea Onofrei; Victor Vlad Costan; Stefan Vasile Toader; Cristina Popa (Romanian Dental Association for Education, 2023)
Angular Cheilitis (AC) represents a multifaceted oral pathology characterized by erythematous lesions at the labial commissures. Despite its prevalence, AC is often inadequately addressed due to its polymorphic etiology, which can encompass infectious agents, nutritional deficits, and systemic conditions. This article provides a systematic review of the pathophysiology, clinical presentation, and etiological factors of AC, including nutritional deficiencies, infectious agents, and systemic diseases. Emphasizing a multidisciplinary strategy, we discuss the collaborative roles of dental, medical, and dermatological expertise in the accurate diagnosis and effective management of AC. We outline diagnostic criteria, appropriate laboratory tests, and imaging techniques tailored to address the multifaceted nature of the condition. Management strategies encompass a range of options from topical treatments and medications to dietary modifications and preventative measures, with an emphasis on evidence-based practices. This review advocates for integrated care models to optimize treatment efficacy, patient compliance, and to mitigate the recurrence of AC. Our analysis aims to enhance the understanding of AC and to provide a framework for its management, contributing to better patient care and opening avenues for future research.